Pharmacological mechanisms by which baicalin ameliorates cardiovascular disease - Si, Lujia; Lai, Yu (Frontiers in Pharmacology, 2024)
Baicalin is a flavonoid glycoside obtained from the dried root of Scutellaria baicalensis Georgi, which belongs to the Labiatae family. Accumulating evidence indicates that baicalin has favorable therapeutic effects on cardiovascular diseases. Previous studies have revealed the therapeutic effects of baicalin on atherosclerosis, myocardial ischemia/reperfusion injury, hypertension, and heart failure through anti-inflammatory, antioxidant, and lipid metabolism mechanisms. In recent years, some new ideas related to baicalin in ferroptosis, coagulation and fibrinolytic systems have been proposed, and new progress has been made in understanding the mechanism by which baicalin protects cardiomyocytes. However, many relevant underlying mechanisms remain unexplained, and much experimental data is lacking. Therefore, further research is needed to determine these mechanisms. In this review, we summarize the mechanisms of baicalin, which include its anti-inflammatory and antioxidant effects; inhibition of endothelial cell apoptosis; modulation of innate immunity; suppression of vascular smooth muscle cells proliferation, migration, and contraction; regulation of coagulation and fibrinolytic systems; inhibition of myocardial hypertrophy; prevention of myocardial fibrosis; and anti-apoptotic effects on cardiomyocytes.